Aggregate Stability and Soil Moisture Improvements Influenced by Chicken Manure Applied on Ultisol and Cabbage (Brassica oleraceae L.) Growth - Candra Ardian; Bambang Gonggo Murcitro; Marwanto Marwanto; Hesti Pujiwati; Prasetyo Prasetyo (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2022)
Cultivation problems on marginal Ultisol involved low soil organic matter content, low water holding capacity and low soil aggregate stability. These constraints determined cabbage growth because of root crop development limited and plant nutrient uptake inhibited. Application of chicken manure could overcome the marginal constraints through improving soil aggregate stability and soil moisture content on the marginal Ultisol as well as the cabbage growth increased. The purpose of this study was to evaluate the soil aggregate stability and soil moisture in Ultisol as affected by the chicken manure applied and the cabbage growth improvement. This study was conducted from December to February, 2021 at Agriculture Station, Faculty of Agriculture, University of Bengkulu lying on ±100 m above sea level. The experiment design used was Completely Random Block Design (CRBD) with the chicken manure applied involved 5 doses; 7.5 tons ha-1, 15 tons ha-1, 22,5 tons ha-1, 30 tons ha-1, and without the manure as a control treatment. From the variance analysis (ANAVA) in the level of 5%, the chicken manure applied was significantly influence the improvement of soil aggregate stability and soil moisture content as well as the cabbage growth. With Duncan Multiple Range Test (DMRT), the dose of 7.5 tons ha-1 gave the highest value of the soil aggregate and soil moisture improvement. Furthermore, the chicken manure application of 7.5 tons ha-1 improved significantly the cabbage stem diameter at the age of 15 days, 30 days, and 45 DAP. The 7.5 tons ha-1 manure applied also gave significantly a number of leaves at the age of 15 days and 30 DAP. The height of plant was significantly influenced when the cabbage growth 15 DAP with 15 tons ha-1. In short, the chicken manure applied with 7.5 tons ha-1 gave the soil aggregate stability, the soil moisture, and cabbage growth improvement.